ADAB AL-ATHFAL FI KITAB AL-QIRAÃH AL-RASYIDAH (DIRASAH FI AL-QIYAM AL-DINIYYAH) - Al Anshory, Abdul Muntaqim; Munjiah, Ma'rifatul (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
This study aims to determine the form of children's literature and religious values in the book al-Qira'ah al-Rasyidah Volume 1. This research is qualitative research with a content analysis approach. The data was collected through documentation techniques. The data was further analyzed using qualitative data analysis techniques, including data reduction, data presentation, and drawing conclusions or verification. The results showed that: (1) children's literature containing religious values in the book Al-Qira'ah al-Rasyidah Volume 1 contained in 13 stories, with various forms of children's literature, namely: realism (stories of realism and animal stories), traditional literature (fable), and fantasy literature (fantasy stories), (2) religious values contained in children's literature in the book al-Qira'ah al-Rasyidah Volume 1 generally takes the form of worship and morals, namely: responsibility, loving plants, sincerity, not making animals wrong, empathizing like visiting sick people, not looking down on others, positive thinking, diligently working, using time well, honesty, not sacrificing the interests of others for personal gain, keep promises, diligent, educate children wisely, cooperative and not selfish.